2017
DOI: 10.4049/jimmunol.1700515
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Modulates Macrophage Responses to Mycobacterium tuberculosis Infection through Activation of HIF-1α and Repression of NF-κB

Abstract: IFN-γ is essential for control of Mycobacterium tuberculosis infection in vitro and in vivo. However, the mechanisms by which IFN-γ controls infection remain only partially understood. One of the crucial IFN-γ target genes required for control of M. tuberculosis is Inducible nitric oxide synthase (iNOS). While nitric oxide (NO) produced by iNOS is thought to have direct bactericidal activity against M. tuberculosis, the role of NO as a signaling molecule has been poorly characterized in the context M. tubercul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
121
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(131 citation statements)
references
References 47 publications
(73 reference statements)
5
121
0
1
Order By: Relevance
“…Considering the role of HIF‐1α −/− in the transcriptional control of the macrophages responses, we next investigated if the susceptibility of mHIF‐1α −/− mice was caused by an altered expression of protective molecules in the lungs. To this end, we measured the expression of IFN‐γ and antimycobacterial genes induced by IFN‐γ, including that for iNOS (encoded by Nos2 ) and that for the immunity‐related GTPase family M member 1 gene ( Irgm1 ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the role of HIF‐1α −/− in the transcriptional control of the macrophages responses, we next investigated if the susceptibility of mHIF‐1α −/− mice was caused by an altered expression of protective molecules in the lungs. To this end, we measured the expression of IFN‐γ and antimycobacterial genes induced by IFN‐γ, including that for iNOS (encoded by Nos2 ) and that for the immunity‐related GTPase family M member 1 gene ( Irgm1 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies suggest that HIF‐1α is a central regulator of the macrophage response to mycobacterial infections . One particular study showed that mice deficient in HIF‐1α in the myeloid lineage (mHIF‐1α −/− ) were acutely susceptible to aerosol Mtb Erdman challenge .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Anand and colleagues found that hypoxia or genetic overexpression of HIF-1α enhances phagocytic capacity of activated macrophages, partially by promoting the p38-MAP kinase signaling pathway [59]. More recently, Bravermand and Stanley showed that inducible nitric oxide synthase (iNOS) activates HIF-1α in a NO-dependent manner to form a positive feedback loop amplifying antimicrobial activity [60]. During infection with Mycobacterium tuberculosis , which establishes latency in macrophages, NO was previously thought to have bactericidal activity against the infection.…”
Section: Mechanisms Of Hif-1α Stabilization Activation and Degradatmentioning
confidence: 99%
“…During infection with Mycobacterium tuberculosis , which establishes latency in macrophages, NO was previously thought to have bactericidal activity against the infection. Instead, they found that NO acts a signaling molecule downstream of IFN-γ to stabilize HIF-1α and promote M. tubercuolosis killing indirectly [60]. …”
Section: Mechanisms Of Hif-1α Stabilization Activation and Degradatmentioning
confidence: 99%
See 1 more Smart Citation